2018
DOI: 10.1111/jphs.12228
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Information, Brand, Medical Representatives and Sales Promotion on Physician Prescribing Decision

Abstract: Objectives There is a lot of debate over the influence of marketing efforts on the prescribing decisions of physicians. Accordingly, this study is an attempt to determine the influence of four marketing efforts (available information on a drug, brand of a drug, medical representatives (MRs) and sales promotion) on the drug prescribing decisions of physicians in Yemen. Method A survey research was conducted among physicians in Yemen. A total of 393 usable questionnaire responses were analysed using partial leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…One of the most critical factors that may affect the prescribing decisions of the physician, regardless of the brand name of the drug, is the performance of the medical representative, who convinces the physicians of the importance of the product to their patients. Additionally, medical representatives can explain in detail about these benefits and the features of the products, which explore the product's superiority compared to competitors' products, and this has been confirmed by several previous studies, (e.g., Murshid & Mohaidin, 2018: Basile, 2019Musleh and AL-Dmour, 2011), which confirmed the positive effect of the performance of medical representatives on the prescribing decisions of physicians.…”
Section: Study Problem and Questionssupporting
confidence: 69%
See 4 more Smart Citations
“…One of the most critical factors that may affect the prescribing decisions of the physician, regardless of the brand name of the drug, is the performance of the medical representative, who convinces the physicians of the importance of the product to their patients. Additionally, medical representatives can explain in detail about these benefits and the features of the products, which explore the product's superiority compared to competitors' products, and this has been confirmed by several previous studies, (e.g., Murshid & Mohaidin, 2018: Basile, 2019Musleh and AL-Dmour, 2011), which confirmed the positive effect of the performance of medical representatives on the prescribing decisions of physicians.…”
Section: Study Problem and Questionssupporting
confidence: 69%
“…The results of the study confirmed that there is no statistically significant effect for the performance of the medical representatives on the relationship between the brand equity and the prescribing decisions of physicians, and it is clear that the brand equity plays a greater role on influencing the prescribing decisions of physicians, regardless of the abilities of the medical representative. Murshid and Mohaidin (2018) confirmed the absence of a positive and statistically significant role in the performance of the medical representative on the prescribing decisions of physicians, as the effect of the performance was negative and this effect is not statistically significant. This study suggests that a strong and relevant brand with a good reputation plays a positive role in the mind of the doctor more than the performance of medical representatives does to convince physicians to prescribe medicines from these companies.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations